العقيدة والهرطقة في الفكر المسيحي قراءة نقدية لموقف يوحنا الدمشقي من الإسلام في كتابه الهرطقات المئة (Journal of the College of Basic Education, 2024)
The multiplicity of readings of religious texts has led to a multiplicity of opinions within religion as well as outside it. With religions fearing that their internal structure will be infiltrated because criticism is internal, they have imposed strict penalties to limit these ideas that contradict the official reading. Through our research, we attempt to shed light on an important dialectic between freedom of opinion and the accusation of heresy in Christianity, which considers ideas that differ from its beliefs to be a departure from the general context of religion and a violation of its doctrinal necessities. The research begins by shedding light on the ancient texts that accompanied the emergence of Islam in its early days, which are among the oldest texts that represent the Christian-Islamic debate. It is the work of the monk John of Damascus, known as the Flow of Gold, through his book "The Hundred Heresies", which had a great impact in missionary and orientalist circles.